Os processos de avaliação de livros didáticos no Brasil: (1938-1984) - Filgueiras, Juliana Miranda (2011)
This study aims to analyze the textbook evaluation processes in Brazil, by their historical perspective since the 1930 s, when the first nationally organized evaluation process was established. During this research four major periods related to the textbook national policies were identified, as well as different evaluation processes. The first process was established by law no. 1.006 of 1983, which created the Comissão Nacional do Livro Didático, the CNLD (Brazilian Textbook Commission). The second process happened during the 1950´s, when the Campanha do Livro Didático e Manuais de Ensino, the Caldeme (Textbooks and Teaching Manuals Campaign), was created. The third moment took place during the military dictatorship in 1966 with the creation of the Comissão do Livro Técnico e do Livro Didático, the Colted (Technical Book and Textbook Commission). The last moment started in 1971, when the Colted was extinguished and its functions were transferred to the Instituto Nacional do Livro, the INL (National Book Institute), which started the Programa do Livro Didático (Textbook Program) and the manuals co-edition processes until 1976. After that the Programa do Livro Didático (Textbook Program) was transferred to the Fundação Nacional do Material Escolar, the Fename (School Material National Foundation). The research is concluded with the extinction of the co-edition system in the 1980 s. The objective of this thesis was to identify those involved in the dispute field over the school manuals, what were the activities and interests of these agents, also highlighting the conflicts and struggles over this field. Based in authors as Chervel, Goodson and Choppin, the analysis allowed the verification of the importance of didactic manuals in the schooling process, in the school subjects teaching and learning relation. The exam of different evaluation processes showed the intention of different social groups to control the content disclosed by textbooks, showing the value of this instrument in education as a tool for standardizing and harmonizing culture